Penerapan Model Pembelajaran Problem Based Learning Pada Materi Sistem Pernapasan Manusia Untuk Meningkatkan Hasil Belajar Siswa Kelas V SD GMIT Kuanino 2 Kota Kupang - Kendrick Mira Higa; Hartoyo Yudhawardana; Rista Apriliya Devi (STKIP Subang, 2026)
This research aims to improve student learning outcomes through the application of the Problem based Learning model to human respiratory system materials. This research is motivated by the low learning outcomes of grade V students of SD GMIT Kuanino 2 Kupang City. The research is motivated by the low learning outcomes of students in the material of the human respiratory system, this occurs because teachers are still dominant in learning, while students tend to be passive, lack concentration, and have not been actively involved in group discussions. The research uses the Classroom Action Research (PTK) method with two cycles, each consisting of planning, action, observation, and reflection stages. Data was collected through observation sheets and tests, then analyzed descriptively. The results showed that in the first cycle only 9 students (40.85%) were completed, while 12 students (57.14%) were not completed due to lack of focus and participation. In cycle II, learning outcomes increased to 19 students (90.47%) who were complete, supported by activeness, enthusiasm, concentration, and cooperation in groups. Meanwhile, 2 students (9.52%) who had not completed the enrichment program were given an enrichment program by the homeroom teacher. Thus, the application of the PBL model has been proven to have a positive impact on learning outcomes, as shown by an increase in completeness from 40.85% in cycle I to 90.47% in cycle II. Keywords:Problem Based Learning, Human Respiratory System, Learning Outcomes